Karakteristik dan Tingkat Kemandirian Lansia di Panti Sosial Rehabilitasi Lanjut Usia (RSLU) Pemerintah Provinsi Jawa Barat - Susan Susyanti; Dais Lukman Nurhakim (Jurnal Medika Cendikia, 2019)
Changes in brain structure will be experienced by the elderly, it’s causing a setback in the quality of life that has implications for independence in activity. The existence of these changes can lead to deterioration in the quality of health of the elderly both physically and psychologically, causing an impairment in the elderly's independence. The purpose of this study is to know the description of the characteristics and level of independence of the elderly in West Java Provincial Government Hospital. The research method uses quantitative descriptive of the survey approach. The sample size is 62 elderly with non random sampling technique in the form of accidental sampling. Characteristic data collection by filling in questions based on the results of elderly answers, while data on the level of independence is collected using the observation sheet which is checked list in accordance with the elderly answers. The results showed that most of the elderly (72.6%) were female, the majority of the elderly (58.1%) had lived in elderly homes for > 1 year, most of the health conditions of the elderly (51.6%) were in the sick category, almost as determined elderly (38.7%) included in the advanced category (elderly), most of the elderly (56.4%) were at moderate levels of independence. Conclusion, most of the elderly at the elderly homes are women, living > 1 year, sick condition, moderate level of independence and almost half are included in the elderly category. Suggestions for nurses to do more guidance in the form of elderly independence training, so that within its limitations the elderly are able to do their daily activities independently.